Single crystal X‐ray structure determination and temperature‐dependent structural studies of the smectogenic compound 7OS5. Issue 6 (7th December 2020) - Deptuch, Aleksandra; Jaworska-Gołąb, Teresa; Kusz, Joachim; Książek, Maria; Nagao, Keigo; Matsumoto, Takashi; Yamano, Akihito; Ossowska-Chruściel, Mirosława D.; Chruściel, Janusz; Marzec, Monika
Abstract : Determination of an orthorhombic crystal structure in a solid phase of smectogenic compound 7OS5 (4‐ n ‐pentylphenyl‐4′‐ n ‐heptyloxythiobenzoate) is reported. Polymorphism in the solid and liquid crystalline phases is investigated by complementary methods. Abstract : Structural characteristics of solid and liquid crystalline phases of 7OS5 (4‐ n ‐pentylphenyl‐4′‐ n ‐heptyloxythiobenzoate), the achiral smectogenic mesogen with the shortest terminal carbon chain in the n OS5 homologous series, are studied by complementary methods. Simultaneously perfomed X‐ray diffraction and differential scanning calorimetry occur to be a powerful tool to study metastable phases. The single crystal structure of a high‐temperature phase, supercooled from the room temperature down to −183°C [orthorhombic crystal system; space group Pca 21 ; a = 54.285 (5) Å, b = 5.5843 (3) Å, c = 14.841 (1) Å, Z  = 8] is determined. Lamellar ordering of elongated molecules is stabilized by hydrogen bonds . Temperature dependence of unit‐cell parameters in two crystal phases as well as structural parameters of liquid crystalline phases (smectic layer spacing, tilt angle, average distance between the long axes of molecules and correlation lengths) are determined by X‐ray diffraction. The obtained results are compared with the data available for other compounds in the n OS5 homologous series.